2021
DOI: 10.1186/s13195-021-00842-3
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing beta-3 adrenergic receptor agonists for Alzheimer’s disease: beneficial effects in a mouse model

Abstract: Background Old age, the most important risk factor for Alzheimer’s disease (AD), is associated with thermoregulatory deficits. Brown adipose tissue (BAT) is the main thermogenic driver in mammals and its stimulation, through β3 adrenergic receptor (β3AR) agonists or cold acclimation, counteracts metabolic deficits in rodents and humans. Studies in animal models show that AD neuropathology leads to thermoregulatory deficits, and cold-induced tau hyperphosphorylation is prevented by BAT stimulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 112 publications
1
9
0
Order By: Relevance
“…Although no studies have reported a relation between β3-AR agonists and PS1 or BACE-1, the beneficial role of a β3-AR agonist against Aβ was reported in a model of AD, where it helped to avert the Aβ-induced memory loss, whereas the effect of a β2 agonist was more limited ( Gibbs, 2015 ). Previous studies, both these co-authors and others, also reached the same conclusion, where activation of β3-AR, but not β2, reduced Aβ and its production and prevented the associated memory loss in an AD model ( Gibbs et al, 2010 ; Tournissac et al, 2021 ); these facts support our findings. The failure of β2-AR agonists to mediate similar effects may be owed to the binding of β2-AR to Aβ leading to its dysfunction and degeneration ( Wang et al, 2011 ), a finding that can explain the effect of the β2-AR blocker carvedilol.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although no studies have reported a relation between β3-AR agonists and PS1 or BACE-1, the beneficial role of a β3-AR agonist against Aβ was reported in a model of AD, where it helped to avert the Aβ-induced memory loss, whereas the effect of a β2 agonist was more limited ( Gibbs, 2015 ). Previous studies, both these co-authors and others, also reached the same conclusion, where activation of β3-AR, but not β2, reduced Aβ and its production and prevented the associated memory loss in an AD model ( Gibbs et al, 2010 ; Tournissac et al, 2021 ); these facts support our findings. The failure of β2-AR agonists to mediate similar effects may be owed to the binding of β2-AR to Aβ leading to its dysfunction and degeneration ( Wang et al, 2011 ), a finding that can explain the effect of the β2-AR blocker carvedilol.…”
Section: Discussionsupporting
confidence: 91%
“…Amyloidosis is known to accompany AD centrally, but no direct role in ulcerative colitis has yet been reported. Nevertheless, the association between dementia and patients with IBD ( Zhang et al, 2021 ) and the beneficial role of β3 agonism for AD ( Tournissac et al, 2021 ) has been recently highlighted. In addition, earlier studies reported that Aβ or its precursor was present in the enteric neurons of patients with AD ( Shankle et al, 1993 ; Puig et al, 2015 ; Yi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…133 Tau pathology was not affected by administration of the β3AR agonist but there was a 27% reduction of the insoluble Aβ42/Aβ40 ratio in the hippocampus of 3xTg-AD mice. 133 This collection of experimental results demonstrates that beta-blockers have been found to be associated with both decreased or increased AD pathology and risk. Additionally, it has been shown that agonism of beta-adrenergic receptors can also be bene-ficial on AD pathology development.…”
Section: Adrenergic Drugs and Reduction Of Ad Risk And Pathologymentioning
confidence: 85%
“…Animal studies have revealed that selective activation of β 1 -AR activates the cAMP/PKA/CREB pathway to rescue social memory deficit in APP mice ( Coutellier et al, 2014 ), as well as inhibiting the expression of neuroinflammatory markers (e.g., ionized calcium binding adapter molecule 1) and reducing Aβ and tau pathology in 5 × FAD mice ( Ardestani et al, 2017 ). Moreover, treatment with CL-316243, a β 3 -AR agonist, could reduce Aβ pathology and reverse memory loss ( Gibbs et al, 2010 ; Tournissac et al, 2021 ; Table 2 ). Therefore, the current consensus is that pharmacological activation of β 1 - and β 3 -ARs is beneficial in AD.…”
Section: Noradrenergic Systemmentioning
confidence: 99%